Language, literature and critical practice ways of analysing text - Birch, David (Interface (London, England)., 1989)
Using a wide-ranging variety of texts the author reviews and evaluates a broad range of approaches to textual commentary, introducing the reader to the fundamental distinction between `actual' and `virtual' worlds in critical practice.